The relationship between education and income inequality (the case of Pakistan) - Rehman, Seema; Rashidi, Muhammad Zaki (International Journal of Accounting and Economics Studies, 2017)
The Income Inequality refers to the unequal distribution of family or individual wealth among the inhabitants of a particular economy. It is often determined by the percentage of income to a percentage of population. Like 50% of Pakistan’s income is controlled by the highest 20% population. It is generally thought of as “unjust," if the major share of a country’s income goes to the rich. Many researches have been done to find the level of Income Inequality in Pakistan, but these researches are not comparable because of differences in techniques, selection of welfare determinant, choice of data (individual or family incomes) and difference in indices for inequality measurement. It is also observed that two studies give contradictory results for the same period. This research tries to fill the gap by measuringthe impact of education on unequal distribution of income in Pakistan. The study uses Gini Coefficient method to measure Income Inequality in Pakistan by taking data available at the websites of PSLM (Pakistan Social and Living Standards Measurement Survey), HIES (Household Income and Expenditure Survey) and MDG’s (Pakistan Millennium Development Goals).This This paper tries to determine the effects of various components of education on Income Inequality. Progress in education is judged by assessing three indicators: Primary Enrolment Rate, Completion Rate (grades 1-5) and Adult Literacy Rate. In this research, we define Adult Literacy Rate as Tertiary Rate as it includes population of ages 15 years and older. The pooled cross sectionaldata considered in this study is for the periods 2004/05, 2007/08 and 2010/11 The results of regression are as expected, which shows an unambiguously negative association between Primary Enrolment Rate andIncome inequality, however, as concluded by Barro (1996), it is validated that inequality increases with higher education. Therefore, an increase in schooling helps distributes income justifiably.